2021
DOI: 10.1098/rsbl.2021.0298
|View full text |Cite
|
Sign up to set email alerts
|

Are parrots naive realists? Kea behave as if the real and virtual worlds are continuous

Abstract: Human psychology and animal cognition have increasingly used virtual stimuli to test cognitive abilities, with the expectation that participants are ‘naive realists’, that is, that they perceive virtual environments as both equivalent and continuous with real-life equivalents. However, there have been no attempts to investigate whether nonhuman subjects in fact behave as if physical processes in the virtual and real worlds are continuous. As kea parrots have previously shown the ability to transfer knowledge b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Previous studies have shown that kea can transfer learned discriminations from object to picture and vice versa (Wein et al 2015 ), but find it easier to discriminate between real than digital objects in a reversal-learning task (O’Hara et al 2015b ). A recent study investigated whether kea can perceive the real and virtual world as continuous, i.e., that a virtually displayed process can have a real physical impact (Bastos et al 2021c ). Kea could observe a seesaw tilting to one side, which resulted in a token rolling off the seesaw and falling into one of two containers.…”
Section: Physical Cognitionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that kea can transfer learned discriminations from object to picture and vice versa (Wein et al 2015 ), but find it easier to discriminate between real than digital objects in a reversal-learning task (O’Hara et al 2015b ). A recent study investigated whether kea can perceive the real and virtual world as continuous, i.e., that a virtually displayed process can have a real physical impact (Bastos et al 2021c ). Kea could observe a seesaw tilting to one side, which resulted in a token rolling off the seesaw and falling into one of two containers.…”
Section: Physical Cognitionmentioning
confidence: 99%
“…Half of the kea avoided virtual tokens when it seemed to touch but not fall into a real box (proximity control). The authors argued that this suggests that kea perceive virtual environments as equivalent and continuous with the physical world (Bastos et al 2021c ).…”
Section: Physical Cognitionmentioning
confidence: 99%
See 1 more Smart Citation